2016
DOI: 10.1371/journal.pone.0160067
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Responses to L-Glutamine of Livers from Rats with Diabetes Types 1 and 2

Abstract: There are several claims about the beneficial effects of supplementing L-glutamine to both type 1 and type 2 diabetes. The purpose of the present study was to provide detailed knowledge about the fate of this amino acid in the liver, the first organ that receives the compound when ingested orally. The study was done using the isolated perfused rat liver, an experimental system that preserves the microcirculation of the organ and that allows to measured several parameters during steady-state and pre steady-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…A clinical study has found a significant positive correlation between the plasma level of glutamate and insulin resistance, and an increase in glutamine/glutamate ratio predicted a reduced risk for developing diabetes. , Increased glutamine and decreased glutamate might be associated with increased levels of glucagon-like peptide-1, enhancement of the vesicle trafficking of GLUT4, and improvement in insulin secretion and insulin sensitivity. , In our current study, the M group had a significantly lower glutamine/glutamate ratio compared to the groups Con and ND, and the treatment with the purple potato anthocyanin extract rich in acylated anthocyanins significantly increased the glutamine/glutamate ratio, indicating improved insulin secretion and/or insulin sensitivity. The nonacylated bilberry anthocyanin extract did not show clear impact on the glutamine/glutamate ratio.…”
Section: Discussionsupporting
confidence: 50%
“…A clinical study has found a significant positive correlation between the plasma level of glutamate and insulin resistance, and an increase in glutamine/glutamate ratio predicted a reduced risk for developing diabetes. , Increased glutamine and decreased glutamate might be associated with increased levels of glucagon-like peptide-1, enhancement of the vesicle trafficking of GLUT4, and improvement in insulin secretion and insulin sensitivity. , In our current study, the M group had a significantly lower glutamine/glutamate ratio compared to the groups Con and ND, and the treatment with the purple potato anthocyanin extract rich in acylated anthocyanins significantly increased the glutamine/glutamate ratio, indicating improved insulin secretion and/or insulin sensitivity. The nonacylated bilberry anthocyanin extract did not show clear impact on the glutamine/glutamate ratio.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand, an intra-portal load of L-glutamine in rat with experimentally-induced type 1 DM generates increased glucose output, accompanied by enhanced urea and ammonia production [40]. These might be providing a background to explain the enhanced blood levels for ammonia and urea found in our patients with type 2 DM ( Figs 1, 2, 4 and 5 ).…”
Section: Discussionmentioning
confidence: 76%
“…The glucose output in livers from D, DG and DIR+G was high after starting perfusion with KH alone, but with a continuous decline up to 30 min. This phenomenon mainly reflects glucose release from the glycogen stores, which are usually higher in diabetic animals (Comar et al, 2016). The declining rates of glucose and lactate at the beginning of the perfusion (0-30 min) can be best appreciated by evaluating the AUC, which correspond to the total amounts released during the initial 30 min.…”
Section: Liver Metabolismmentioning
confidence: 99%